Tourism Communication In The Development Of Jagara Eco Park Tourism Destination Based On Community Empowerment - Ramdani, Fadli; Imawan, Khaerudin; Andriany , Dian (Green Publisher Indonesia, 2025)
This study discusses tourism communication strategies in the development of Jagara Eco Park destinations based on community empowerment using the Public Relations (PR) theory approach. The main focus of the study is on traffic congestion that arises due to increased tourist visits. With a descriptive qualitative approach and in-depth interviews, this study shows that effective PR communication can build synergy between managers, the community, and other stakeholders in overcoming negative impacts such as traffic jams. The importance of the role of PR in building a positive image, managing public opinion, and establishing long-term relationships with various parties for the sake of tourist destinations is emphasized.